Oxidation of Flavonols in an Electrochemical Flow Cell Coupled Online with ESI‐MS. Issue 5 (8th December 2015) - Kummer, Sina; Ruth, Wolfgang; Kragl, Udo
Abstract: Flavonols, a class of flavonoids, are jointly responsible for antioxidant activities as free radical acceptors in flowers, fruits and vegetables. Due to their electroactive behaviour, the oxidation of chrysin, flavonol, kaempferol, morin, quercetin and myricetin in methanol was performed in an electrochemical flow cell with glassy carbon as the working electrode. This flow cell was coupled online with electrospray ionisation mass spectrometry to identify the possible oxidation products. Based on these experiments, it was concluded that when certain structural requirement are present, the initial electrode reaction of flavonols involves an electron delivery electrochemical step followed by a chemical step via methanol addition. The redox activity of the selected species explains the number of observed multiple methoxylation. Moreover, we identified a second two‐electron, two‐proton oxidation of the formed oxidation products of quercetin and myricetin for the first time. Abstract :